The Ecology and Burrow Architecture of Ghost Crab at Selected Beaches Around Kuching Division - Asyraf Ahamed, Bin Basheer Ahamad (Universiti Malaysia Sarawak (UNIMAS), 2011)
Ghost crabs are macroinvertebrates under the Genus Ocypode is active at nigJ-lt foraging for food and live in a burrow. Generally, they live at the sandy beach and widely found in the tropical and subtropical regions of the world. Ghost crab is a pest for turtle conservation and protection sanctuary in Malaysia. Documentation about ghost crabs' ecology and burrow architecture are necessary for future research and effective marine turtle management. Therefore, this research aimed to identify the burrow shape of ghost crab according to beach profile, and establish relationship of burrow architecture with sediment type. Study has been conducted at beaches around Kuching division which are Sematan beach, Siar beach and Pandan beach. Utilization of Plaster of Paris and Polyester Resin is useful to obtain the burrow shape. Among the shapes obtained in this study were J, J, U, G and spiral shape with the burrows mostly found in high tide and middle tide zone. Sediment analysis shows that Pandan beach has high coarse sand percentage but Sematan and Siar beach has high fine sand percentage. The burrow shape and bioglyphs were determined by sediment type and the shape varied according to sediment type, sexes, species and size. The ghost crab species found in this study was OC,vpode ceratolphthalmus based on the ghost crab caught from the burrow.